Arbutin encapsulated micelles improved transdermal delivery and suppression of cellular melanin production. (December 2016) - Liang, Ke; Xu, Keming; Bessarab, Dmitri; Obaje, Jonathan; Xu, Chenjie
Abstract Background Hyperpigmentation is a skin disorder characterized by elevated production of melanin. Current treatment approaches mainly rely on the application of skin lightening chemicals, most of which have safety issues. Efficacy of delivery of the active ingredients to the target organ has also been a challenge. Transdermal based drug delivery platform has been shown to improve drug bioavailability, avoiding the hepatic first pass metabolism, decrease gastrointestinal side effects, and eventually enhance patient compliance. Results This article explores the utilization of micellar transdermal delivery technology to improve skin penetration and efficacy of arbutin, a hyperpigmentation agent. The suppression efficacy of cellular melanin production versus cell viability of four active ingredients commonly used in skin lightening products, namely allantoin, arbutin, glycolic acid, and hyaluronic acid were first compared. Arbutin was selected for the micellar delivery studies base on its comparatively low cytotoxicity and better performance in reducing melanin production. Micellar Arbutin cream was formulated using Urah® proprietary micellar technology and was assessed for its cellular melanin suppression efficacy and skin penetration capacity. Conclusion The results show that micellar arbutin cream improved both the delivery and cellular melanin suppression, suggesting that micellar transdermal delivery may have potential application in addressing hyperpigmentation skin disorders.Graphical abstract Transdermal delivery of arbutin with micelles for melanin production suppression.